Analysis of the Effectiveness of Health Worker Services in Health Administration - Mariani, Tia; Agustina, Dewi; Susilawati, Susilawati (Indonesian Journal of Global Health Research, 2024)
Excellent service in the context of hospitals means assistance provided to patients based on quality standards to meet the needs and desires of patients so that patients can get satisfaction which can ultimately increase their trust in hospitals. But in terms of service, a number of hospitals in North Sumatra, especially those managed by the government, are often complained about by the public. There are many unscrupulous hospital employees who openly discriminate and are picky in helping patients. This study aims to determine how the effectiveness of health administration officer services at the inpatient registration of the Medan Hajj General Hospital. This research uses qualitative research using a case study approach through observation, interviews and documentation to 4 informants conducted intensively and in depth. The results showed that the effectiveness of administrative officers in the registration section at the Medan Hajj General Hospital was very good. However, the facilities in the waiting room are not sufficient. The results showed that the effectiveness of administrative officers in the registration section at the Medan Hajj General Hospital has not realized online registration. and the facilities in the waiting room are not sufficient.